2004
DOI: 10.1038/sj.onc.1207395
|View full text |Cite
|
Sign up to set email alerts
|

Frequent loss of RUNX3 gene expression in human bile duct and pancreatic cancer cell lines

Abstract: RUNX3, a Runt domain transcription factor involved in TGF-b signaling, is a candidate tumor-suppressor gene localized in 1p36, a region commonly deleted in a wide variety of human tumors, including those of the stomach, bile duct, and pancreas. Recently, frequent inactivation of RUNX3 has been demonstrated in human gastric carcinomas. In this study, to examine the involvement of RUNX3 abnormalities in tumorigenesis of bile duct as well as pancreatic cancers, we investigated not only the expression but also met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 21 publications
3
48
1
Order By: Relevance
“…line MKN28, breast cancer line MCF-7, prostate cancer line LNCap, colon cancer line DLD1, and pancreatic cancer line MiaPaca2, EZH2 mRNA was suppressed with EZH2 siRNA in all five cancer cell lines, in which RUNX3 is silenced (7,11,12,27,28 (Fig. 1A, f-j).…”
Section: Ezh2 Down-regulates Runx3mentioning
confidence: 96%
See 2 more Smart Citations
“…line MKN28, breast cancer line MCF-7, prostate cancer line LNCap, colon cancer line DLD1, and pancreatic cancer line MiaPaca2, EZH2 mRNA was suppressed with EZH2 siRNA in all five cancer cell lines, in which RUNX3 is silenced (7,11,12,27,28 (Fig. 1A, f-j).…”
Section: Ezh2 Down-regulates Runx3mentioning
confidence: 96%
“…2B) (7,11,12,27). We then investigated whether the status of DNA methylation in the RUNX3 promoter region changed after knockdown of EZH2 and resulted in restoration of RUNX3 gene expression.…”
Section: Ezh2 Down-regulates Runx3mentioning
confidence: 99%
See 1 more Smart Citation
“…RUNX2 (AML-3) is essential in osteogenesis (Komori et al, 1997;Fujita et al, 2004;Yoshida et al, 2004), whereas RUNX3 (AML-2) has important functions in neurogenesis Levanon et al, 2002), growth regulation of gastric epithelial cells (Li et al, 2002), TGF-b signalling (Shi and Stavnezer, 1998;Fainaru et al, 2004) and thymopoiesis (Taniuchi et al, 2002;Woolf et al, 2003). Recent studies have shown that loss of RUNX3 expression, usually through allelic loss and epigenetic changes, is associated with hepatocellular carcinoma, testicular yolk sac tumours, gastric and pancreatic cancers (Guo et al, 2002;Kato et al, 2003;Wada et al, 2004;Xiao and Liu, 2004), RUNX3, therefore, has important tumour suppressor function as an integral part of TGFb apoptotic signalling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies revealed that the frequent reduction of RUNX3 expression levels is also observed in several human cancers such as lung cancer, breast cancer, colon cancer, pancreatic cancer, and prostate cancer, which might be attributed to promoter hypermethylation (7)(8)(9)(10)(11)(12)(13), indicating that the down-regulation of RUNX3 is not restricted to gastric cancer. Intriguingly, Yano et al (15) demonstrated that, during transforming growth factor-␤-mediated apoptotic cell death, RUNX3 has an ability to transactivate pro-apoptotic Bim (Bcl-2-interacting mediator of cell death) (14) in gastric cancer-derived cell lines.…”
mentioning
confidence: 99%